Spatialisation in Audio Augmented Reality using Finger Snaps - Gamper, Hannes; Lokki, T. (Principles and Applications of Spatial Hearing, 2011)
In audio augmented reality (AAR) information is embedded into the user's surroundings by enhancing the real audio scene with virtual auditory events. To maximize their embeddedness and naturalness they can be processed with the user's head-related impulse responses (HRIRs). The HRIRs including early (room) reflections can be obtained from transients in the signals of ear-plugged microphones worn by the user, referred to as instant binaural room impulse responses (BRIRs). Those can be applied on-the-fly to virtual sounds played back through the earphones. With the presented method, clapping or finger snapping allows for instant capturing of BRIR, thus for intuitive positioning and reasonable externalisation of virtual sounds in enclosed spaces, at low hardware and computational costs.